Analisi Dampak Bisnis Internasional Terhadap Pertumbuhan Perekonomian Di Indonesia - Mico Ferdyansyah; Hendra Ibrahim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
International Trade is an economic transaction carried out between countries. Among the items commonly stored are consumer goods, such as televisions and clothing; capital goods, such as machinery, raw materials and food. In almost all countries, international trade is an effort to increase GDP. Economic growth is an increase in the ability of a country's economy to produce both goods and services in quantity. In general, the high or low population of a country, the birth rate and death rate greatly influence a country's economy because productivity, education, and investment in physical capital since improving longevity create greater needs. The type of research used is qualitative research, qualitative research is research that produces several findings that cannot be obtained using statistical procedures or quantitative methods. With the existence of International Business in Indonesia, Economic Growth will increase. The reason is that the supply and increase for foreign products from the Indonesian people will continue to increase. For this reason, companies or industries in Indonesia will often experience increases and growth, such as the development of the textile, shrimp, coffee and so on industries. With the existence of international business, the prosperity and welfare of society in Indonesia is developing well due to the opening of various kinds of employment opportunities, so that there can be a reduction in the level of poverty in Indonesia.